Natural nanoparticle complexes at water-water interfaces - Han Wang; Yi Lu; Long Bai; Mengqi Zhu; Xiyue Liu; Zhiguo Li; Yang Liu; Wei Li; Shouxin Liu; Siqi Huan; Chaoji Chen; Thomas P. Russell; et al. (Nature Communications)
Abstract Aqueous two-phase systems (ATPSs) with multifunctional attributes have significant promise as biomimetic materials, but current approaches do not harness their full potential. Here, we show that ATPSs can be stabilized to form microcapsules by the interfacial assembly of chitin nanofibers (ChNF) and rod-like cellulose nanocrystals (CNC). The high structural stability of the ChNF/CNC complexes integrates permeability and transport across the membrane at the liquid/liquid interface. Driven by density and osmotic stress gradients, the microcapsules show switchable motility, including cyclic meniscus-climbing and subsurface transport. These observations demonstrate a self-regulating system with potential for cargo transfer, cell biomimicry, as well as ATPSs-based microreactors and microrobots.